Membangun Adaptasi Santri Baru Melalui Pendekatan Cognitive Behavioral Therapy Islamic di Pondok Pesantren - Tohir, Toha; Fauzi, Ahmad; Ulfah, Yeniati (LP3M STIT Al Urwatul Wutsqo Jombang, 2025)
This study is in the field of Islamic educational psychology and aims to build the adaptation of new students in the Islamic boarding school environment through the Cognitive Behavioral Therapy Islamic (CBT-I) approach. Adaptation is an initial challenge often experienced by new students, marked by the emergence of anxiety, social difficulties, and culture shock that have an impact on the learning process and personality development. CBT-I was chosen because it integrates cognitive-behavioral techniques with Islamic values, which are relevant to the context of Islamic boarding schools. This study uses a descriptive qualitative method with a case study approach to a number of new students in one of the Islamic boarding schools in West Java. Data were collected through observation, in-depth interviews, and documentation. The results showed that the application of CBT-I helped students recognize negative thoughts, build positive beliefs based on Islamic values, and improve social and emotional abilities. This study contributes to the development of an Islamic-based psychological intervention model in the Islamic boarding school environment. The conclusion shows that CBT-I is effective in supporting the adaptation process of new students, and this approach is important to be applied more widely to support the psychological well-being of students holistically.